The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3122/jabfm.2017.03.160321
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Health Coaching by Medical Assistants in Primary Care

Abstract: Background Health coaching is potentially a practical method to assist patients in achieving and maintaining healthy lifestyles. In health coaching, the coach partners with the patient, helping patients discover their own strengths, challenges, and solutions. Methods Two medical assistants were provided with brief training. The 12-week program consisted of telephone coaching with in-person visits at the beginning and end of the program. Coaching targeted improvements in diet, physical activity, and/or sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
0
16
0
3
Order By: Relevance
“…Some pilot programs have found improvements in cancer screenings 4,6 , cholesterol levels 21 , diabetes control 11,21 , medication adherence 19 , physical activity levels and body mass index. 9 However, Ferrer and colleagues 2 found that there was poor adoption of MA health coaching, and several randomized trials testing the effects of MA diabetes health coaches found no significant differences in hemoglobin A1C levels or hospitalizations between control and intervention group patients. 10,13,15,18 There is currently a limited understanding as to why there was success in some studies and not others.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some pilot programs have found improvements in cancer screenings 4,6 , cholesterol levels 21 , diabetes control 11,21 , medication adherence 19 , physical activity levels and body mass index. 9 However, Ferrer and colleagues 2 found that there was poor adoption of MA health coaching, and several randomized trials testing the effects of MA diabetes health coaches found no significant differences in hemoglobin A1C levels or hospitalizations between control and intervention group patients. 10,13,15,18 There is currently a limited understanding as to why there was success in some studies and not others.…”
mentioning
confidence: 99%
“…5 They also serve as health coaches to improve lifestyle behaviors 9 , chronic disease care processes 3,10 -18 , and medication adherence. 19 These innovative MA roles have been reported across diverse settings, including private practices 2,3,5,20 , community health centers 5,10,13,15,16,19 , academic primary-care practices 8,9,12,14 , rural practices 17 , and large health care systems. 4,5,7 Outcomes in studies that have focused on or included MA role expansion or innovation have varied.…”
mentioning
confidence: 99%
“…Ha mostrado además resultados positivos en varios estudios, incluida la pérdida de peso, el control de la diabetes, la disminución de la presión arterial y mejoría en los comportamientos en salud 12 . También se ha visto la disminución en el tiempo invertido bajo la supervisión de un profesional de la salud, el incremento en la satisfacción de los usuarios por la entrega de un tratamiento personalizado, y un aumento en la confianza en el equipo de salud, cuando fue aplicada la metodología del coaching 12,13 .…”
Section: Coaching En Salud Y Coaching Nutricionalunclassified
“…Dado que el foco del trabajo con el paciente no es el problema de salud en sí, sino que su comportamiento, puede que la baja de peso si es lo esperado no ocurra de manera inmediata, lo que podría ser desalentador. Sin embargo, al focalizarse en las actitudes del paciente, es esperable que en las sesiones sucesivas, distintos aspectos de su vida vayan mejorando, siendo uno de ellos el manejo de sus conductas en salud, lo que se manifestará finalmente en los parámetros esperados 12,20,21 .…”
Section: Coaching En Salud Y Coaching Nutricionalunclassified
“…In this pilot study, Djuric et al 11 report positive weight-loss outcomes in the 49% of patients who completed 12 weeks of coaching. Overall, small differences were found at the end of the study.…”
Section: Decision: Use Medical Assistant Health Coaching For Lifestylmentioning
confidence: 99%